New roles for desmin in the maintenance of muscle homeostasis - Agnetti, Giulio; Herrmann, Harald; Cohen, Shenhav (Febs Journal, 2021)
Desmin is the primary intermediate filament (IF) of cardiac, skeletal, and smooth muscle. By linking the contractile myofibrils to the sarcolemma and cellular organelles, desmin IF contributes to muscle structural and cellular integrity, force transmission, and mitochondrial homeostasis. Mutations in desmin cause myofibril misalignment, mitochondrial dysfunction, and impaired mechanical integrity leading to cardiac and skeletal myopathies in humans, often characterized by the accumulation of protein aggregates. Recent evidence indicates that desmin filaments also regulate proteostasis and cell size. In skeletal muscle, changes in desmin filament dynamics can facilitate catabolic events as an adaptive response to a changing environment. In addition, post-translational modifications of desmin and its misfolding in the heart have emerged as key determinants of homeostasis and disease. In this review, we provide an overview of the structural and cellular roles of desmin and propose new models for its novel functions in preserving the homeostasis of striated muscles.
CRIS-Team Scopus Importer:2021-05-07
Keywords: desmin intermediate filaments; GSK3; heart failure; metabolism; muscle atrophy; protein degradation; protein misfolding